Cooperative learning and group learning: The impact on high order thinking skills in the pythagorean theorem material - Suri, Fraulein Intan; Osella, Sonnia; Masykur, Ruhban; Widyastuti, Rany (Desimal: Jurnal Matematika, 2023)
This study aims to improve students High Order Thinking Skills through the application of the Group to Group Exchange learning model. The research method used is a quasi-experimental model with a Pretest-Posttest Control Group research design and a sampling technique using Cluster Random Sampling. The results showed that based on the research results obtained during the study, the average N-Gain Score for the experimental group using the Group to Group Exchange learning model was 59% with a minimum N-Gain Score of 51% and a maximum of 67%. While the average N-Gain Score control group with the Direct Instruction learning model is 39% with a minimum N-Gain Score of 34% and a maximum of 45%. This means that the Group to Group Exchange (GTGE) learning model is quite effective compared to the Direct Instruction (DI) learning model to improve students High Order Thinking Skill (HOTS).